A sensitivity analysis on the heating and cooling energy flexibility of residential buildings. (January 2020) - Vivian, Jacopo; Chiodarelli, Umberto; Emmi, Giuseppe; Zarrella, Angelo
Highlights: Energy flexibility of residential buildings assessed in heating and cooling season. New buildings have reduced CADR in heating mode and increased in cooling. New buildings have higher ηADR compared to old ones in both seasons. Best timing of ADR events emerged with some exceptions. Different events may significantly affect comfort conditions especially in winter. Abstract: The present paper evaluates the potential of the buildings thermal inertia to modify their heat load pattern using two energy flexibility indicators: the available heat storage capacity and the efficiency of active demand response events. The study analyses the effects of building envelope, user behaviour and weather conditions on the flexibility indicators for three reference apartments. The results show that during the heating season the available storage capacity increases from new to old buildings. Part of the thermal energy shifted is lost through the envelope after the events, resulting in lower efficiencies for old buildings. In general, upwards and downwards modulation events are preferable just before and just after the peak load periods, respectively. The paper shows that severe weather conditions and intermittent set-point schedules lead to exceptions to this general rule. In the heating season, forced modulation events do not bring to significant variation of thermal comfort in well-insulated buildings, whereas they do in old ones. During the cooling season, the choice of the best event is more difficult due to the high variability of diurnal heat gains and the indoor thermal conditions depend on the start time of events rather than on the type of building envelope.